Assessment of the drinking water quality from natural sources in the Kharkiv city - Lisnyak, A. A.; Kulyuk, M. I. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2022)
Improving the reliability and quality of the population's drinking water supply is one of the primary social problems, since the health of the population largely depends on the level of safety of drinking water.Purpose. To determine the composition of spring drinking water consumed by residents of different districts of the city of Kharkiv and to compare the assessment of the quality of drinking water from different natural sources.Methods. Field, laboratory-analytical, statistical.Results. Water samples from 5 natural springs in the city of Kharkiv, from which the population collects water for drinking purposes, were studied. It was determined that according to the organoleptic indicators, no excesses of the normative values are observed, the pH almost does not change seasonally, with the exception of the sample from the "Nemyshlianske" source. The analysis of total alkalinity in the autumn period showed that the standard was exceeded only in samples of the source of the Yunist park and along the street. Klochkivska, and in the spring period - only in the sample of the source on the street. Klochkivska. The total hardness in the samples ranges from 4.9 to 8.04 mmol/dm3 in the autumn period, and from 6.6 to 10.4 mmol/dm3 in the spring period. Excesses in chloride content are not observed in any of the investigated water samples. The iron content exceeds the MPC level only in water samples from the Nemyshlianske spring. The content of aluminum, zinc, cadmium, copper, lead, ammonia and nitrites in the samples is significantly below the MPC level, and almost does not change by season.Conclusions. The formation of the general quality class of water samples from natural sources is significantly influenced by the high level of total alkalinity, total hardness, and iron content in some sources of non-centralized water supply. According to the integral ecological index of water samples in the autumn period from natural sources "Nemyshlyanske", Park "Yunist" and along the street. Klochkivska belongs to the II quality class, i.e. pure water. The integrated ecological index for all other water samples in the autumn period assigns these sources to the I class of water quality - very clean. The calculation of the integral ecological index for water samples from all natural sources in the spring period refers them to the II quality class.